Chapter Strategic Planning Document of Port Authority System, a new city-ports agreement: the case of Northern Tyrrhenian Sea AdSP - Palano, Isabella (Proceedings e report, 2020)
Legislative Decrees 169/16 and 232/17 have modified Law 84/94. The changes introduces the Port System Regulatory Plan, composed of the PRPs of the individual ports and the Strategic System Planning Document. Among the contents of the DPSS, for which institutional agreements between AdSP and territorial bodies are envisaged, there is the identification of the so-called "Areas of port-city interaction". The objective of this research is to propose a methodology for identifying the areas of influence of the port on the city, measuring the degree of interaction through a system with indicators.